PENINGKATAN KUALITAS AIR SUMUR BOR DENGAN PENDEKATAN DMAIC - valen, Kevin siambaton; Sirait, Ganda (LPPM Universitas Putera Batam, 2022)
Water is a basic necessity for every living thing on this earth. wells are containers used to hold water and are used for daily life. at this time the extraction of well water has used a vacuum, known as the wellbore. the water used for human needs must be guaranteed its quality which is generally seen from the physical, chemical and biological. the quality of drinking water must be in accordance with government standards, basically proper consumption water is colorless, not turbid and clear. the use of bore well water as raw material for distilled into drinking water, the quality of bore well water still does not meet the established standards, therefore researchers will improve the quality of bore well water with a DMAIC approach. DMAIC is define, measure, analyze, improve and control. DMAIC methods will help to improve the quality of wellbore water according to government standards. Keyword: drinking water, improve, quality, standardization, water, wellbore